Urbanization and rainfall-runoff relationships in the Milwaukee River Basin - (:unkn) unknown (My University, 2016)
To understand the changing rainfall-runoff relationship, the study examined climate and streamflow data in the Milwaukee River Basin in southeastern Wisconsin, of which four catchments with different degrees of urbanization were selected for analysis. This study analyzed temperature, precipitation, and streamflow data with a range of statistical methods, including the Mann-Kendall test, double-mass technique, and quantile regression. Runoff ratios and extreme flow indices were higher in more urbanized catchments. Catchments with long-term data (>40 years) showed significantly increasing runoff ratios and slopes in double mass curves. Overall, there are signs of changes in the rainfall-runoff relationship, but how much they can be attributed to land use changes is uncertain.
Keywords: runoff; precipitation; streamflow; urbanization; Milwaukee